STEPS FOR PREDICTING STRATEGIC RISKS - Примшиц, Виктория (Modern engineering and innovative technologies, 2017)
The paper discusses approaches and the need to forecast strategic risks. The stages of forecasting strategic risks are determined based on the study of factors and the construction of a risk map.